KONSEP EKONOMI PANCASILA - Zainol Hasan (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2021)
Pancasila is a philosophy as well as a source of law for all policies that are a reference for state administration, including in the economic field. The Pancasila economy is an economic concept that is explored and built from the values adopted in Indonesian society. It is also built on the values that exist in Indonesian society. That is derived from religious values, norms, customs, or culture. Even though the world economy has become unified and the market has become global, as long as there is an Indonesian nation and state, the concept of Pancasila economy is still dedicated to the Indonesian people. In addition, the economic concept of Pancasila is not only materialistic but also faith and piety. This is moral and ethical for the administration in the economic field. Therefore, the concept of Pancasila economy is controlled by moral and ethical principles